(untitled) (Research, Society and Development, 2023)
Objective: To describe, based on the scientific literature, the behaviors and difficulties of nurses when dealing with cancer patients. Methodology: This is an integrative literature review, carried out from September to October 2022, using the following database: LILACS, SCIELO, PUBMED, contemplated by the VHL, where articles in Portuguese or English were used. Results: A total of 1720 articles were found, after methodological rigor through the inclusion and exclusion criteria, 11 articles were selected, 5 articles in LILACS, 3 in SCIELO and 3 in PUBMED, soon after a careful evaluation of the articles, the analysis was done in a descriptive way and predisposes the extraction of the following data: year of publication, authors, title and objective, where all articles highlight the importance of nursing care, emotional support to cancer patients and palliative care. Conclusion: Therefore, it was possible to observe the importance of communication between the nursing professional and the patient, in addition to extended care for family members and the professional himself, since the same professional who cares needs to be cared for. It is essential for the nursing team to assist the patient and family in a holistic way, not focusing only on the disease, as already mentioned, but it should always be borne in mind that people are biopsychosocial beings and have varied demands in the areas of their lives.